231k views
7 votes
Solve the following equation: -3 = 1 3/5 + m.

2 Answers

7 votes
  • -3=1 -3/5+m
  • -3=8/5+m
  • m=-3-8/5
  • m=-15-8/5
  • m=-23/5
  • m=-4 3/5
User El Yobo
by
5.9k points
9 votes

Answer:


\sf m=-4 (3)/(5)

Explanation:


\sf -3=1 (3)/(5)+m


\sf \implies -3=1+(3)/(5)+m

Subtract 1 from both sides:


\sf \implies -3-1=1+(3)/(5)+m-1


\implies \sf -4=(3)/(5)+m

Subtract 3/5 from both sides:


\implies \sf -4-(3)/(5)=(3)/(5)+m-(3)/(5)


\implies \sf -4-(3)/(5)=m


\implies \sf -\left(4+(3)/(5)\right)=m


\implies \sf m=-4 (3)/(5)

User Steve Ruble
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.